Sex Education in Implementation of Merdeka Curiculum at Early Childhood Education - Anwar, Nur Amalia Olby; Purwastuti, Lusila Andriani (Universitas Pendidikan Ganesha, 2024)
The Ministry of Women’s Empowerment and Children Protection stated that Indonesia is currently facing an emergency regarding sexual violence against children. This statement is based on the record of increasing cases of sexual violence against children. One effort to prevent sexual violence is by providing sexual education. The aim of this research was to analyze the concept and pattern of implementing sexual education in the implementation of the Independent Curriculum in early childhood education. This research used a qualitative approach with research type of case study. Data collection techniques were carried out using interview, observation, and documentation methods. Data sources in this research included: the principal, 2 Play Group teachers, 2 Group A teachers, 2 Group B teachers, 1 teacher specializing in sexual education topic, and 3 parents of students. The analysis technique used was the six stages of qualitative analysis techniques according to Creswell. The research results showed that the implementation of sexual education in the implementation of the Merdeka Curriculum is actually a manifestation of learning outcome, which is carried out through several activities, namely toilet training, habituation of the rules for changing clothes, communication in daily life, and special sex education classes. Massive implementation of sexual education should involve all school members and parents of students in order to create sustainable sexual education.